Incêndios naturais no Cerrado e a produção sustentável de commodities: análise da pegada de carbono - Dutra, Darissa Alves (2024)
Although fires are an intrinsic element of the Cerrado biome, changes in the fire regime have caused ecological imbalances, culminating in the manipulation of the ecosystem and substantial emissions of carbon dioxide (CO2). The biome can be recognized as an epicenter of agricultural production in Brazil. The production of Saccharum officinarum (sugarcane), Coffea arabica (coffee), and Bos taurus (cattle) for beef cattle has become crucial to the Brazilian economy, with these activities being very conditional in the Cerrado. In this sense, the research had the following objectives: (i) to promote measures to mitigate the occurrence of these fires in the Cerrado, (ii) to evaluate the carbon footprint of two agricultural scenarios and one livestock scenario in areas degraded by natural fires in the biome; (iii) to perform the carbon balance of these production systems; and, (iv) to analyze these agricultural productions from an economic perspective The results indicated a contrast, natural fires emit less carbon (0.427 tCO2eq) compared to agricultural activities, coffee (4.4 tCO2eq) sugarcane (2.9 tCO2eq), and livestock (5.2 tCO2eq). However, agricultural production in areas degraded by natural fires represents the most favorable scenarios, with substantial potential for reduced environmental impact evidenced by a negative carbon balance, -57 tCO2eq for sugarcane and -2.5 tCO2eq for o coffee, associated with a generation of economic return, coffee generates a higher income (USD 3256), followed by sugarcane (USD 1941) and livestock (USD 364). This research drives progress in restoring ecosystems degraded by natural fires in the Cerrado biome, pointing to a promising trajectory for developing resilient and sustainable agrifood systems.